Pembuatan Peta Wilayah Nagari Tanjung Gadang Berbasis Pemetaan Digital sebagai Program Kerja KKN di Kecamatan Lareh Sago Halaban, Kabupaten Lima Puluh Kota, Provinsi Sumatera Barat - Armaita Armaita; Linika Larasati; Mario Siregar; M. Sechan Dwi Apsa; Mhd. Amru Inuwan Hasibuan; Rajul Muttaqin Caniago; Rafido Rahma (CV. ITTC INDONESIA, 2026)
The absence of digitized administrative maps in rural areas remains a significant obstacle to transparent and data-driven village governance. This study aims to describe the process of creating a digital administrative map of Nagari Tanjung Gadang, Lareh Sago Halaban District, Lima Puluh Kota Regency, West Sumatra Province, as part of the Kuliah Kerja Nyata (KKN) community service program. A systematic and participatory approach was applied, encompassing four stages: preparation and literature review, field data collection, digital map processing using Geographic Information System (GIS) software, and finalization and handover. Field surveys were conducted over 14 working days, producing 187 GPS coordinate points across five spatial categories. The resulting map comprises five primary layers—administrative boundaries, road networks, land use, public facilities, and hydrology—totaling 312 spatial features, and was completed in 21 working days, ahead of schedule. The map received positive responses from village officials and was immediately utilized in the preparation of the Village Medium-Term Development Plan (RPJMNag). This study demonstrates that digital mapping technology, when integrated with a participatory community engagement approach, can effectively address spatial data gaps in rural areas and strengthen the capacity for independent village governance.